Research on the statistical analysis of basketball games - Shan, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The research is important to three 2008 Olympic tasks (basketball information and science service for the 2008 Beijing Olympics Games. Research on the skills and tactics of the top male basketball teams and knowledge of their attack and defence tactics is useful in the preparation of teams for major events. As a function of analysis of basketball games at home and overseas this paper aims to find the differences in theory and practice with respect to the analysis of statistics associated with basketball games. Methods A comprehensive search of the literature was undertaken together with interviews of experts. Logical analysis and comparative analyses were also undertaken. Results According to the theory and methods of game analysis in basketball China is behind compared to the level found in other countries. Based on the broad classical theory, the research constructs a rudimentary analysis system for basketball game data from eight aspects. Discussion / Conclusions Based on shots, points, rebound performance, turnovers, efficiency of attack and defense, the five-man unit, clutch moment performance and accomplish in goal of game, the research analyzed shot performance from shooting opportunity, shooting distractions, shooting field goal rated and attack period. The study analyzed points, through points per possession and opponent points per possession. The study investigated the rebound performance through team performance and player performance. When it comes to a turnover, turnovers per possession and points from turnover. Evaluation of the efficiency of attack and defence was through points per hundred possessions. According to different five-man units, the method can enable discussion of the performance of different units. Consultation with coaches can occur by performance in clutch moments. The study findings can assist coaches by providing information to accomplish the goals of the game.